2010
DOI: 10.1111/j.1440-1746.2009.06216.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of microRNA in the inflamed colonic mucosa of patients with active ulcerative colitis

Abstract: Upregulated miRNA may be responsible for the development of intestinal inflammation in UC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
112
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(122 citation statements)
references
References 20 publications
6
112
0
4
Order By: Relevance
“…When comparing the lists, no miRNA duplicates were found. Several of the differentially expressed miRNAs (such as miR23a, miR-155, miR-16, miR-150, miR-346, and miR-126) reported to be associated with UC in previous studies [36][37][38] were also identified within our analyses (Tables 2 and 3). However, in addition to these previously reported miRNAs, we additionally identified five potential miRNAs, miR-20b, miR-99a, miR-203, miR-26b, and miR-98 to be differentially up-regulated more than a 10-fold in active UC compared to inactive UC, active CD, inactive CD, and controls (Table 2).…”
Section: Statistical Analysis Mirna Data Analysissupporting
confidence: 54%
See 1 more Smart Citation
“…When comparing the lists, no miRNA duplicates were found. Several of the differentially expressed miRNAs (such as miR23a, miR-155, miR-16, miR-150, miR-346, and miR-126) reported to be associated with UC in previous studies [36][37][38] were also identified within our analyses (Tables 2 and 3). However, in addition to these previously reported miRNAs, we additionally identified five potential miRNAs, miR-20b, miR-99a, miR-203, miR-26b, and miR-98 to be differentially up-regulated more than a 10-fold in active UC compared to inactive UC, active CD, inactive CD, and controls (Table 2).…”
Section: Statistical Analysis Mirna Data Analysissupporting
confidence: 54%
“…Among the miRNAs with the strongest differential power from the microarray expression data we identified several differentially expressed miRNAs (such as miR23a, miR-155, miR-16, miR-150, miR-346, and miR-126) previously reported to be associated with UC [36][37][38] . However, we also identified seven miRNAs (miR-20b, miR99a, miR-203, miR-26b, miR-98, miR-125b-1*, and let7e*) that were not previously reported to be involved in IBD [27] .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they found that miR192 participated in the regulation of chemokine production in colonic epithelial cells. Since 2008, some new research in active UC and healthy controls has confirmed the upregulation of miR-21 [25,118] , miR 29a [119] , and miR126 [120] , and identified additional upregulated miRNAs, including miR7, miR29b, miR126*, miR1273p, miR135b, miR223 and miR 3243p [119] , miR31 [119,121] , miR150 [26] , miR155 [118] , miR146a, miR206, and miR424 [121] , and miR 20b and miR125b1* [122] . In contrast, miR1885p, miR215, miR320a, miR346 [119] , and miR200b [123] were downregulated in colon tissues from active UC patients compared with healthy controls.…”
Section: Mirnas In Ucmentioning
confidence: 99%
“…При активном ЯК изменялась экспрессия 11 микроРНК (miR-16, miR-21, miR-23a, miR-24, miR-29a, miR-126, miR-195, miR-let-7f, miR-192, miR-375, and miR-422b), осо-бое внимание обращено на изменение экспрессии miR-192. После публикации этого исследования, по-явились другие работы, целью которых была иденти-фикация микроРНК, определение патогенетической роли микроРНК и выяснение закономерностей экс-прессии микроРНК в генезе ЯК и БК [52].…”
Section: лабораторные биомаркеры язвенного колитаunclassified
“…Экспрессия miR-155 повышается при ЯК [52], сле-дом увеличивается и синтез ФНО-α. В перспективе ученые планируют использовать этот факт в созда-нии иммуноподавляющей мишени терапии.…”
Section: лабораторные биомаркеры язвенного колитаunclassified